OP03 Telaprevir-based therapy in G1 HCV-infected patients with prior null response, partial response or relapse to peginterferon/ribavirin: REALIZE trial final results. (6th September 2011) - Foster, G; Zeuzem, S; Andreone, P; Pol, S; Lawitz, E; Diago, M; Roberts, S; Focaccia, R; Younossi, Z; A H,; Heeswijk, R V; de Meyer, S; et al.
Abstract : Introduction: This Phase 3 study evaluated telaprevir (T) in combination with pegylated-IFN alfa-2a (P) and ribavirin (R) in well-characterised G1 prior-PR treatment failure patients including prior PR non-responders (null and partial) and relapsers. Method: REALIZE was a randomised, international, multicentre, double-blind, placebo-controlled trial evaluating efficacy, safety and tolerability of T (750 mg q8 h) plus P (180μg/w) and R (1000–1200 mg/d) compared with PR alone. The treatment arms (randomised 2:2:1, stratified by viral load and prior response) were: 12-weeks T/PR, followed by 36-weeks PR (T12PR48); 4-weeks PR followed by 12 weeks T/PR (T delayed start, DS), then 32-weeks PR (T12(DS)/PR48); 48-weeks PR (Pbo/PR48). The primary objective was efficacy of the T/PR arms in non-responders and relapsers. Secondary objectives included evaluation of T DS and efficacy in prior-null and -partial responders. HCV RNA was quantified using COBAS TaqManÆ v2.0 assay (LLOQ=25 IU/ml). Results: 833 patients were screened, and 662 treated. 70% of patients were male, 93% Caucasian, 26% had cirrhosis, and 89% had baseline HCV RNA ≥800 000 IU/ml. AEs reported more frequently in T arms were rash, pruritus, diarrhoea, anorectal disorders and anaemia. 13% of T/PR patients had premature discontinuation (D/C) of T due to AEs: rash (4%) and anaemia (3%) were the most common AEs leading to T D/C. Conclusion: T/PR SVR was significantly superior to PR in all prior-treatment failure populations including null- and partial-responders. A telaprevir delayed start did not have a significant impact on SVR rates. Safety profile of T/PR was consistent with that observed in treatment naive subjects.